Transcriptome differences in frontal cortex between wild boar and domesticated pig. (13th March 2018) - Long, Keren; Mao, Ke; Che, Tiandong; Zhang, Jinwei; Qiu, Wanling; Wang, Yujie; Tang, Qianzi; Ma, Jideng; Li, Mingzhou; Li, Xuewei
Abstract: Animal domestication is a long‐term, multistage process that results in modifications of many traits, especially the less aggressive behavior in domesticated animals. In this study, we used the Illumina RNA‐seq to compare the transcriptome in brain frontal cortex between wild boar and Rongchang pig, a typical indigenous domestic pig in China, and revealed that 604 genes and 639 genes were specifically detected in wild boar and domesticated pig, respectively, with distinct functional characteristics that may be related to their respective environment. In addition, we identified 60 differentially expressed genes showing an enrichment in immune response‐related function. Further comparison of the results against previous studies identified seven genes that are associated with domestication. Our results provide insights for deciphering the mechanism of pig domestication in the future.